2020
DOI: 10.1001/jamadermatol.2019.4315
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fetal Safety Outcomes and Exposure to Local Podophyllotoxin During Pregnancy

Abstract: IMPORTANCEPodophyllotoxin is an antimitotic agent primarily used in the local treatment of anogenital warts. Data that enable the assessment of the fetal safety of podophyllotoxin use during pregnancy are lacking.OBJECTIVE To investigate the association between local podophyllotoxin exposure during pregnancy and risk of adverse fetal outcomes. DESIGN, SETTING, AND PARTICIPANTSThis cohort study obtained individual-level pregnancy data from various nationwide registries in Denmark from the study period of Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“… 13 Podophyllotoxin and imiquimod were prohibited during pregnancy because their fetal teratogenic effect was grade C for pregnancy medication classified by FDA. 126 However, a cohort study 127 showed that there was no statistical relationship between podophyllotoxin exposure and nonexposure groups in birth defects, spontaneous abortion, preterm delivery, and stillbirth. The study concluded that the use of podophyllotoxin during pregnancy (the dose of podophyllotoxin was not specified in this cohort study, and exposure was based on the prescription of the drug) did not increase the risk of adverse fetal outcomes.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Podophyllotoxin and imiquimod were prohibited during pregnancy because their fetal teratogenic effect was grade C for pregnancy medication classified by FDA. 126 However, a cohort study 127 showed that there was no statistical relationship between podophyllotoxin exposure and nonexposure groups in birth defects, spontaneous abortion, preterm delivery, and stillbirth. The study concluded that the use of podophyllotoxin during pregnancy (the dose of podophyllotoxin was not specified in this cohort study, and exposure was based on the prescription of the drug) did not increase the risk of adverse fetal outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…At present, no self-applied topical agent is licensed for use during pregnancy or breastfeeding. Although recent safety data for imiquimod and podophyllotoxin are reassuring, 94,96 there is insufficient evidence to recommend either for routine use given the availability of safe and effective alternatives.…”
Section: Pregnancy and Breastfeedingmentioning
confidence: 99%
“…The use of podophyllin is contraindicated in pregnancy. However, a recent analysis of 9229 pregnancies from January 1997 to December 2016 showed that podophyllotoxin didn't appear to be associated with an increased risk of adverse events to the fetus during pregnancy and is probably safe for use during pregnancy [38].…”
Section:  Podophyllinmentioning
confidence: 99%